Single and multiple dose pharmacokinetics and pharmacodynamics of omarigliptin, a novel, once‐weekly dipeptidyl peptidase‐4 inhibitor, in healthy Japanese men. Issue 1 (8th July 2016) - Tsuchiya, Saori; Friedman, Evan; Addy, Carol; Wakana, Akira; Tatosian, Daniel; Matsumoto, Yuki; Suzuki, Hideyo; Kauh, Eunkyung
Abstract : Omarigliptin is a novel, potent, long‐acting oral dipeptidyl peptidase‐4 (DPP‐4) inhibitor being developed as a once‐weekly (q.w.) treatment for type 2 diabetes (T2DM) patients, with 25 mg and 12.5 mg tablets recently being approved as market formulations in Japan. We evaluated the safety, tolerability, pharmacokinetics, and pharmacodynamics of omarigliptin in healthy Japanese male subjects after single and multiple dose administration. Omarigliptin was well tolerated and had a pharmacokinetic and DPP‐4 inhibition profile that supports once‐weekly dosing in Japanese patients with T2DM. Abstract: Aims/Introduction: Omarigliptin is a novel, potent, long‐acting oral dipeptidyl peptidase‐4 inhibitor being developed as a once‐weekly (q.w.) treatment for type 2 diabetes mellitus patients, with 25 mg and 12.5 mg tablets recently being approved as market formulations in Japan. Materials and Methods: This was a two‐part, double‐blind, randomized, placebo‐controlled study in healthy Japanese men to evaluate the safety, tolerability, pharmacokinetics, and pharmacodynamics of omarigliptin after single dose (5–100 mg) and multiple dose (1–50 mg q.w. for 3 weeks) administration. Results: Omarigliptin was rapidly absorbed with a time to maximum concentration of 0.5–4 h. The pharmacokinetic profile was biphasic with a long terminal half‐life >100 h. The area under the concentration–time curve from 0 to 168 h, maximum concentration and the concentration at 168 h post‐dose increased dose‐dependently after 3 weeks of once‐weekly dosing for doses ranging 1–50 mg, with accumulation ratios ranging 1.03–1.35 and 0.87–1.36 for the area under the concentration–time curve from 0 to 168 h and maximum concentration, respectively. Plasma dipeptidyl peptidase‐4 inhibition levels 1 week post‐dose increased with dose, ranging 79.2–94.0% after 5–100 mg single dose administration and 51.3–90.2% after 1–50 mg multiple once‐weekly dose administration. Administration with food did not meaningfully alter the pharmacokinetics of omarigliptin. Omarigliptin was generally well tolerated, with no hypoglycemia being reported. Conclusion: The results of the present study in healthy Japanese men showed that omarigliptin was well tolerated and had a pharmacokinetic and dipeptidyl peptidase‐4 inhibition profile that supports once‐weekly dosing in Japanese patients with type 2 diabetes mellitus.